Inelastic collision dynamics of oriented NO molecules with Kr atoms - Heid, CG; Bentham, IP; Gheorghe, R; Jambrina, PG; Aoiz, FJ; Brouard, M (Taylor and Francis, 2021)
Building on our previous work on NO + Ar, this paper presents a complete set of orientation measurements and quantum mechanical calculations for the NO + Kr collision system, including both spin-orbit conserving and changing collisions, and both side-on (x-axis) and end-on (z-axis) orientations. While many of the trends observed in the oriented differential and integral scattering distributions, as well as in the spin-orbit branching fractions, are similar to the ones seen previously for NO + Ar, a direct comparison with the Ar data reveals subtle differences in the scattering dynamics, which we rationalise with the more extended attractive regions on the NO + Kr potential energy surfaces. High-impact parameter collisions that lead to low scattering angles in the spin-orbit conserving manifold are particularly sensitive to the topology in the attractive parts of the potential, whereas more impulsive, low-impact parameter trajectories, which sample the repulsive parts of the potential, produce very similar features in the oriented differential cross sections for the Ar and Kr systems, especially for spin-orbit changing collisions.